(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objective: To determine the clinical profile and to correlate the sepsis score with blood culture reports in neonatal septicaemia. Methods: Over a period of 6 months (1st week of June to 1st week of December’2005) 50 consecutive newborns with suspected septicaemia were enrolled for the study. It was a prospective study and septicaemia was suspected on the basis of clinical presentation like reluctance to feed, lethargy, fever, abdominal distension etc. Sepsis scoring was done for all of them immediately after enrolment into the study. Investigations like CBC, CRP and blood culture were sent for all the enrolled cases. Then the sepsis scores were compared with their blood culture reports to find out any correlation between them. The data analysis was done by SPSS software. Results: Among the 50 studied babies 31 were male and rest were female. Most of them were delivered by vaginal delivery (74%) but no significant difference was observed among home and institutional delivery. During delivery 24 babies experienced some problems of which 83.3% had perinatal asphyxia. About 59% of the studied babies were not exclusively breastfed. Majority of them (62%) presented with reluctance to feed and 54% were preterm low birth weight. Fever and respiratory distress were present in 19 (38%) and 18 (36%) cases respectively. Forty two percent studied babies had positive sepsis score 5 and above. Regarding correlation of blood culture and sepsis score, 70% culture positive cases had sepsis score 5 and above whereas 35% of culture negative cases had the same score. Sensitivity and specificity of sepsis score was 70 and 65 respectively with CI interval 95%. Conclusion: Sepsis score can be considered as an useful tool in the diagnosis of neonatal septicaemia specially where there is lack of investigational facilities. Before using this tool further evaluation is needed involving large sample size. Key words: Neonatal septicaemia, sepsis score, blood culture. DOI: 10.3329/jbcps.v26i2.4185 J Bangladesh Coll Phys Surg 2008; 26: 79-82